Contribution to the Establishment of the IHRF in the State of São Paulo - Ribeiro, Leticia Cristina [UNESP]; Guimaraes, Gabriel Do Nascimento; Oliveira Camargo, Paulo De [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2022)
This letter describes a practical computation to determine the potential values, following the International Association of Geodesy (IAG) recommendations, at Presidente Prudente (PPTE) and Cananeia (NEIA) stations, which are part of the Brazilian Global Navigation Satellite System (GNSS) network, and the first one belongs to the International Height Reference Frame (IHRF) Brazilian network. For the computation, Global Geopotential Models (GGMs) such as EIGEN-6C4, GECO, GOCO05c, and XGM2016 were applied for degree and order 100 and 200. The Least Squares Collocation (LSC), Stokes' Integral, and Hotine's Integral were the methodologies selected in this study. The results were validated in terms of geopotential values, normal heights, and height anomalies. The values obtained present more consistence for the integration radius up to 2 degrees. Moreover, LSC and Hotine's integral showed convergence in the results.
Keywords: Geopotential models; gravity; International Height Reference Frame (IHRF)